Genomic instability and CCNE1 amplification as emerging biomarkers for stratifying high-grade serous ovarian cancer - Conca, Elena; Lorenzini, Daniele; Minna, Emanuela; Agnelli, Luca; Duca, Matteo; Gentili, Marco; Bodini, Beatrice; Polignano, Maggie; Mantiero, Mara; Damian, Silvia; Devecchi, Andrea; Dagrada, Gianpaolo; et al. (Frontiers in Oncology, 2025)
IntroductionOvarian cancer (OC) is one of the leading causes of cancer-related death in women worldwide. Treatment with PARP-inhibitors has significantly improved survival in patients with high-grade serous cancer (HGSC) bearing BRCA1/2 mutations (~22% of the cases), and/or homologous recombination deficiency (HRD, ~50%). Unfortunately, limited therapeutic alternatives are available for BRCA1/2 wild type/HR proficient HGSC patients, who usually exhibit resistance to standard treatments and poor prognosis.MethodsHerein, we present the results of a comprehensive genomic profiling (CGP) analysis using the Oncomine Comprehensive Assay® (OCA) Plus in a consecutive retrospective cohort of 102 HGSC patients characterized in our institution.ResultsGenomic instability, measured by Genomic Instability Metric (GIM) >16, was found in 40% of the cases and was significantly associated with BRCA1/2 mutations (p=0.009), with a better prognosis in terms of recurrence-free survival (p=0.01). CCNE1 amplification was observed in 29% of cases and was negatively correlated with BRCA1/2 mutations (p=0.001), without any association with GIM, supporting CCNE1 as a strong and independent driver of tumorigenesis. Additionally, CCNE1 amplification was validated with fluorescent in situ hybridization (FISH), supporting the analytical robustness of NGS data (rho=0.93), and investigated by immunohistochemistry (IHC), revealing that CCNE1 protein overexpression was observed in the absence of gene amplification in 45% of cases.DiscussionOur real-world study supports the clinical utility of the GIM metric and the analytical validity of CCNE1 amplification, a new promising biomarker for personalizing treatment in HR proficient HGSC patients. The discordance between CCNE1 amplification and protein expression raises intriguing questions about the mechanisms of CCNE1-driven tumorigenesis and warrants further investigation.